Upregulation of Store Operated Ca2+ Channel Orai1, Stimulation of Ca2+ Entry and Triggering of Cell Membrane Scrambling in Platelets by Mineralocorticoid DOCA - Guoxing Liu; Guilai Liu; Kousi Alzoubi; Anja T. Umbach; Lisann Pelzl; Oliver Borst; Meinrad Gawaz; Florian Lang (Karger Publishers, 2014)
Background/Aims: Mineralocorticoid excess leads to vascular injury, which is partially due to hypertension but in addition involves increased concentration of cytosolic Ca2+ concentration in platelets, key players in the pathophysiology of occlusive vascular disease. Mineralocorticoids are in part effective by rapid nongenomic mechanisms including phosphatidylinositide-3-kinase (PI3K) signaling, which involves activation of the serum & glucocorticoid inducible kinase (SGK) isoforms. SGK1 has in turn been shown to participate in the regulation of the pore forming Ca2+ channel protein Orai1 in platelets. Orai1 accomplishes entry of Ca2+, which is in turn known to trigger cell membrane scrambling. Platelets lack nuclei but are able to express protein by translation, which is stimulated by PI3K signaling. The present study explored whether the mineralocorticoid desoxycorticosterone acetate (DOCA) influences platelet Orai1 protein abundance, cytosolic Ca2+-activity ([Ca2+]i), phosphatidylserine abundance at the cell surface and/or cell volume. Methods: Orai1 protein abundance was estimated utilizing CF™488A conjugated antibodies, [Ca2+]i utilizing Fluo3-fluorescence, phosphatidylserine abundance utilizing FITC-labelled annexin V, and cell volume utilizing forward scatter in flow cytometry. Results: DOCA (10 µg/ml) treatment of murine platelets was followed by a significant increase of Orai1 protein abundance, [Ca2+]i, percentage of phosphatidylserine exposing platelets and platelet swelling. The effect on [Ca2+]i, phosphatidylserine abundance and cell volume were completely abrogated by addition of the specific SGK inhibitor EMD638683 (50 µM) Conclusions: The mineralocorticoid DOCA upregulates Orai1 protein abundance in the cell membrane, thus increasing [Ca2+]i and triggering phosphatidylserine abundance, effects paralleled by platelet swelling.